Speech and language development: Knowledge and experiences of foster carers - Golding, Shannon; Williams, Cori; Leitao, Suze (The Speech Pathology Association of Australia Ltd., 2011)
This study aimed to investigate foster carers’ knowledge and experience of speech and language development. Foster carers in Western Australia who provided long-term care for children under the age of 5 were selected to participate. This paper reports on data obtained from 20 foster carers using written postal questionnaires. The questionnaire asked foster carers about their daily routine with their foster child, their knowledge of speech and language development and topics related to speech and language development on which they would like further information. Semi-structured interviews were carried out with a subset of 12 foster carers and the results are presented in Part 2. The findings of this study provide speech pathologists with information regarding the needs of this population in terms of therapy services for children and in terms of educational topics of interest for foster carers.